Did hardening occur among smokers in England from 2000 to 2010?. (28th October 2013) - Docherty, Graeme; McNeill, Ann; Gartner, Coral; Szatkowski, Lisa
Abstract Aims To assess trends in the prevalence of 'hardcore' smoking in England between 2000 and 2010, and to examine associations between hardcore smoking and socio‐demographic variables. Design Secondary analysis of data from the United Kingdom's General Lifestyle Survey (GLF) and the Health Survey for England (HSE). Setting Households in England. Participants Self‐reported adult current smokers resident in England aged 26 years and over. Measurements Hardcore smokers were defined in three ways: smokers who do not want to quit (D1), those who 'usually' smoke their first cigarette of the day within 30 minutes of waking (D2) and a combination of D1 and D2, termed D3. Multivariable logistic regression was used to explore associations between these variables and calendar year, age, sex and socio‐economic status, and P‐values for trends in odds were calculated. Findings The odds of smokers being defined as hardcore according to D3 increased over time in both the GLF (P < 0.001) and HSE (P = 0.04), even after adjusting for risk factors. Higher dependence (D2) was noted in men [odds ratio (OR): 1.19, 95% confidence interval (CI): 1.13–1.24], those of 50–59 years (OR: 1.94, 95% CI: 1.80–2.09) and smokers in lower occupational groups (OR: 2.11, 95% CI: (1.97–2.26). Lack of motivation to quit (D1) increased with age and was more likely in men. Conclusions The proportion of smokers in England with both low motivation to quit and high dependence appears to have increased between 2000 and 2010, independently of risk factors, suggesting that 'hardening' may be occurring in this smoker population.